BEHAVIORAL BIASES PADA INDIVIDUAL INVESTOR DI KOTA PALEMBANG - Agung Anggoro Seto (Jurnal Ilmiah Ekonomi Global Masa Kini)
This study aims to identify and analyze the behavioral biases of individual investors in Palembang City. Data collection techniques used in this study are primary and secondary data taken through interviews, while secondary data obtained through literature literature. The population in this study are all individual investors in Palembang City. The sampling technique using Snowball Sampling and Purposive sampling with the number of samples of 100 respondents. Methods of data analysis  starting from the verification of respondents, followed by indepth interviews. The results of the interview were interpreted and analyzed using descriptive statistics. The results concluded that 63% of individual investors in Palembang experienced overconfidence biases, 21% experienced cognitive dissonance biases. 19% experienced Illusion of control biases, 46% experienced regret aversion biases, 73% experienced representative biases, 53% experienced loss aversion biases and 38% experienced mental accounting biases. Keywords : Behavioral Biases, Individual investor